Implementation of Marzano’s Dimensions of Learning on the Critical Thinking Skills of 10th Grade Students at SMK Muhammadiyah 2 Malang - Yudela, Farida Wardah; Fikri, Muhammad Alimul; Sutiah, Sutiah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
This research aims to explore the implementation of Marzano's dimensions of learning, prompted by the conventional teaching methods still prevalent in the learning process, which primarily involve teacher-centered instruction without active student engagement. This approach has negatively impacted students' critical thinking abilities. The study investigates the application of Marzano's dimensions of learning can give a impact on the critical thinking skills of tenth-grade students at SMK Muhammadiyah 2 Malang. Prerequisite tests including normality and homogeneity tests indicate that the data is suitable for hypothesis testing or t-tests. The results of the t-test show a significance level of p < 0.05, specifically 0.00 < 0.05, suggesting that implementing Marzano's dimensions of learning influences the critical thinking skills of students in tenth grade at SMK Muhammadiyah 2 Malang